Candidate SNP Markers of Familial and Sporadic Alzheimer's Diseases Are Predicted by a Significant Change in the Affinity of TATA-Binding Protein for Human Gene Promoters - Ponomarenko, Petr; Chadaeva, Irina; Rasskazov, Dmitry A.; Sharypova, Ekaterina; Kashina, Elena V.; Drachkova, Irina; Zhechev, Dmitry; Ponomarenko, Mikhail P.; Savinkova, Ludmila K.; Kolchanov, Nikolay (Frontiers in Aging Neuroscience, 2017)
While year after year, conditions, quality, and duration of human lives have been improving due to the progress in science, technology, education, and medicine, only eight diseases have been increasing in prevalence and shortening human lives because of premature deaths according to the retrospective official review on the state of US health, 1990-2010. These diseases are kidney cancer, chronic kidney diseases, liver cancer, diabetes, drug addiction, poisoning cases, consequences of falls, and Alzheimer’s disease (AD) as one of the leading pathologies. There are familial AD of hereditary nature (~4% of cases) and sporadic AD of unclear etiology (remaining ~96% of cases; i.e., nonfamilial AD). Therefore, sporadic AD is no longer a purely medical problem, but rather a social challenge when someone asks oneself: “What can I do in my own adulthood to reduce the risk of sporadic AD at my old age to save the years of my lifespan from the destruction caused by it?” Here, we combine two computational approaches for regulatory SNPs: Web service SNP_TATA_Comparator for sequence analysis and a PubMed-based keyword search for articles on the biochemical markers of diseases. Our purpose was to try to find answers to the question: “What can be done in adulthood to reduce the risk of sporadic AD in old age to prevent the lifespan reduction caused by it?” As a result, we found 89 candidate SNP markers of familial and sporadic AD (e.g., rs562962093 is associated with sporadic AD in the elderly as a complication of stroke in adulthood, where natural marine diets can reduce risks of both diseases in case of minor alleles of these SNPs). In addition, rs768454929, and rs761695685 correlate with sporadic AD as a comorbidity of short stature, where maximizing stature in childhood and adolescence as an integral indicator of health can minimize (or even eliminate) the risk of sporadic AD in the elderly. After validation by clinical protocols, these candidate SNP markers may become interesting to the general population (may help to choose a lifestyle [in childhood, adolescence, and adulthood] that can reduce the risks of sporadic AD, its comorbidities, and complications in the elderly).